Autonomy as a protective factor against the detrimental effects of ego depletion on tennis serve accuracy under pressure - Englert, C.; Bertrams, A. (International Journal of Sport and Exercise Psychology, 2015)
It has been repeatedly demonstrated that athletes in a state of ego depletion do not perform up to their capabilities. We assume that autonomous self-control exertion, in contrast to forced self-control exertion, can serve as a buffer against ego depletion effects and can help individuals to show superior performance. In the present study, we applied a between-subjects design to test the assumption that autonomously exerted self-control is less detrimental for subsequent self-control performance in sports than is forced self-control exertion. In a primary self-control task, the level of autonomy was manipulated through specific instructions, resulting in three experimental conditions (autonomy-supportive: n = 19; neutral: n = 19; controlling: n = 19). As a secondary self-control task, participants executed a series of tennis serves under high-pressure conditions, and performance accuracy served as our dependent variable. As expected, a one-way between-groups ANOVA revealed that participants from the autonomy-supportive condition performed significantly better under pressure than did participants from the controlling condition. These results further highlight the importance of autonomy-supportive instructions in order to enable athletes to show superior achievements in high-pressure situations. Practical implications for the coach-athlete relationship are discussed.